2012
DOI: 10.1128/aem.01758-12
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Hydrolysis and Transport in the Extreme Thermoacidophile Sulfolobus solfataricus

Abstract: Extremely thermoacidophilic microbes, such as Sulfolobus solfataricus, are strict chemoheterotrophs despite their geologic niche. To clarify their ecophysiology, the overlapping roles of endoglucanases and carbohydrate transporters were examined during growth on soluble cellodextrins as the sole carbon and energy source. Strain-specific differences in genome structure implied a unique role for one of three endogenous endoglucanases. Plasmid-based endoglucanase expression promoted the consumption of oligosaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…A recent genetic study of cellodextrin hydrolysis and transport in a derivative of Sul. solfataricus strain 98/2 indicated that the homolog of the maltose transporter (binding protein SSO3053) of strain P2 is required for translocation of cellodextrins comprised of three to eight glucose units (G3 to G8) as well as maltose and, to a limited extent, glucose (501). The previously identified glucose transporter (binding protein SSO2847) was not required for glucose transport in this strain, as demonstrated by the unchanged growth of the deletion strain on glucose.…”
Section: Sulfolobus Solfataricusmentioning
confidence: 86%
“…A recent genetic study of cellodextrin hydrolysis and transport in a derivative of Sul. solfataricus strain 98/2 indicated that the homolog of the maltose transporter (binding protein SSO3053) of strain P2 is required for translocation of cellodextrins comprised of three to eight glucose units (G3 to G8) as well as maltose and, to a limited extent, glucose (501). The previously identified glucose transporter (binding protein SSO2847) was not required for glucose transport in this strain, as demonstrated by the unchanged growth of the deletion strain on glucose.…”
Section: Sulfolobus Solfataricusmentioning
confidence: 86%
“…In these extreme habitats, lignocellulosic biomass from the nearby vegetation can experience chemical transformation in the hot and acid conditions, providing carbon sources to the microbial community of extremophiles. Consistently, several sequences encoding for GH and mono-, di- and oligo-transporters for sugars uptake are present in the genome of S. solfataricus [ 19 , 20 ]. Many of the characterized GHs from S. solfataricus showed potential hemicellulolytic activities (GH1, GH2, GH3, GH5, GH12, GH29, GH31, GH36, GH38, GH116), and even some genetic clusters could suggest the ability to hydrolyze hemicelluloses (e.g., S. solfataricus P2 Open reading frames (SSO), SSO1353 and SSO1354 encoding for enzymes with β-glucosidase/β-xylosidase and β-glucanase/β-xylanase activity, respectively) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 94%
“…They also play important roles in pathogenicity and in maintenance of cell integrity, responses to environmental stresses, cell-to-cell communication, and cell differentiation (Eitinger et al, 2011). Bacteria and archaea harbor diverse ABC exporters important in secretion of extracellular enzymes, polysaccharides, toxins, antimicrobial agents and other compounds (Binet et al, 1997;Omori and Idei, 2003;Davidson and Chen, 2004;Dawson et al, 2007;Cuthbertson et al, 2009;Lalithambika et al, 2012). The gene association of biopolymer degradation enzymes with ABC ex-20 porters, usually within the same operon, facilitates secretion of extracellular enzymes (Omori and Idei, 2003).…”
Section: Interactive Discussionmentioning
confidence: 99%